2020
DOI: 10.1371/journal.pone.0234906
|View full text |Cite
|
Sign up to set email alerts
|

The duodenal microbiome is altered in small intestinal bacterial overgrowth

Abstract: Small intestinal bacterial overgrowth (SIBO) is highly prevalent and is associated with numerous gastrointestinal disorders, but the microbes involved remain poorly defined. Moreover, existing studies of microbiome alterations in SIBO have utilized stool samples, which are not representative of the entire gastrointestinal tract. Therefore, we aimed to determine and compare the duodenal microbiome composition in SIBO and non-SIBO subjects, using duodenal aspirates from subjects undergoing standard-of-care esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 48 publications
1
81
2
1
Order By: Relevance
“…A reduction in alpha diversity in the microbiome may indicate a loss of microbial species in response to different environmental factors (i.e., antibiotics) or a presence of microbial players that may be driving the reduction in diversity. For example, there was increased abundance in Klebsiella and Escherichia/Shigella in small intestinal bacterial overgrowth and a reduced duodenal microbiome diversity (31). Consistent with IBS-A, IBS-C, and Crohn’s disease studies, we found lower relative abundances of the anti-inflammatory microbe F. prasunitzii in individuals with IBS than the healthy cohort (29, 3235).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in alpha diversity in the microbiome may indicate a loss of microbial species in response to different environmental factors (i.e., antibiotics) or a presence of microbial players that may be driving the reduction in diversity. For example, there was increased abundance in Klebsiella and Escherichia/Shigella in small intestinal bacterial overgrowth and a reduced duodenal microbiome diversity (31). Consistent with IBS-A, IBS-C, and Crohn’s disease studies, we found lower relative abundances of the anti-inflammatory microbe F. prasunitzii in individuals with IBS than the healthy cohort (29, 3235).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have attempted to characterize the small bowel microbiome in subjects with SIBO and IBS. A North American study found that SIBO subjects had a 7-8-fold increase in Klebsiella and Escherichia/Shigella compared to non SIBO patients (40). One Indian study, on jejunal aspirate of SIBO and IBS subjects, found that 40% of subjects had Pseudomonas aeruginosa, 6.7% had Acinetobacter baumannii, 13.3% had Acinetobacter lwoffii, 13.3% had Staphylococcus spp, 6.7% had Enterococcus faecalis, 20% had Escherichia coli, 6.7% had Enterococcus faecium, 13.3% had Klebsiella pneumoniae, and 6.7% had Streptococcus spp.…”
Section: Prevalence Of Sibo In Ibsmentioning
confidence: 99%
“…IBS is a complicated disease that display comorbidities of both impairment of GI motility and CNS symptoms. The cause of SIBO in IBS is incompletely understood although several studies demonstrated that some of the indole producing bacteria like Escherichia coli exhibit high abundance in the small intestine of SIBO associated IBS patients (Ghoshal et al, 2014, Leite et al, 2020, Avelar Rodriguez et al, 2019. Our findings raise the possibility that SIBO leads to an increase of microbial tryptophan metabolite production in the small intestine, which then activates Trpa1+EECs to increases intestinal motility and modulate CNS activity through the vagal nerve, resulting in the complex comorbidities of intestinal and psychiatric disorders in IBS.…”
Section: Trpa1+eecs Are Frontline Intestinal Sensorsmentioning
confidence: 77%